2007
DOI: 10.1002/cne.21430
|View full text |Cite
|
Sign up to set email alerts
|

Prosurvival and proapoptotic intracellular signaling in rat spiral ganglion neurons in vivo after the loss of hair cells

Abstract: Neurons depend on afferent input for survival. Rats were given daily kanamycin injections from P8 to P16 to destroy hair cells, the sole afferent input to spiral ganglion neurons (SGNs). Most SGNs die over an approximately 14-week period after deafferentation. During this period, the SGN population is heterogeneous. At any given time, some SGNs exhibit apoptotic markers--TUNEL and cytochrome c loss--whereas others appear nonapoptotic. We asked whether differences among SGNs in intracellular signaling relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(109 citation statements)
references
References 119 publications
9
100
0
Order By: Relevance
“…Otolaryngology-Head and Neck Surgery 150 (4) The loss of SGNs, although not as extensive as the IHC loss, was still apparent. Our results agree with a study by Alam et al, 17 who injected rats with kanamycin alone for 8 days to observe the effect on SGNs. They reported a decrease in SGN density 20 days after the first injection.…”
Section: Discussionsupporting
confidence: 95%
“…Otolaryngology-Head and Neck Surgery 150 (4) The loss of SGNs, although not as extensive as the IHC loss, was still apparent. Our results agree with a study by Alam et al, 17 who injected rats with kanamycin alone for 8 days to observe the effect on SGNs. They reported a decrease in SGN density 20 days after the first injection.…”
Section: Discussionsupporting
confidence: 95%
“…However, it is remarkable that simple delayed loss of Atoh1 or loss of several other transcription factors can cause rapid demise of hair cells leading to the nearly flat epithelium, also observed in many human cases of long term hair cell loss. Equally remarkable is that in most of these mice with genetically induced hair cell loss there is substantial and long lasting innervation of parts of the OC (Fritzsch et al, 2005b, Pan et al, 2011, Xiang et al, 2003), which resembles more with human hearing loss conditions compared to hair cell loss induced by other means (Alam et al, 2007). …”
Section: From Oc To a ‘Placode-like’ Epithelium And Back: Neurosenmentioning
confidence: 99%
“…Thus, the data were fitted to a two-time constant model, shown by the 2 exponential functions (dashed lines) and a combined function (solid line), which suggests an early rapid phase of SG cell degeneration over about the first 2 months of deafness and a slower phase thereafter. An important recent study from investigators at the University of Iowa (Alam and Green, 2005;Alam et al, 2007) demonstrated that there are also 2 phases in the degeneration of SG neurons after ototoxic drug induced deafness in rats, an early phase in which apoptosis is correlated with reduced neurotrophic signaling (reduced CREB phosphorylation) and a later phase (after ~postnatal day 60) when activity in the proapoptotic JNK-Jun signaling pathway is tightly correlated with apoptosis of SG neurons. We hypothesize that the two phases of SG cell degeneration observed in our neonatally deafened cats are correlated with the same mechanisms that underlie the two phases of apoptosis in rats, and further, that these mechanisms may be conserved across species and may be relevant to the human cochlea as well.…”
Section: Data From Animal Models Suggest Two Phases In Spiral Gangliomentioning
confidence: 99%